Wolbachia infection in field-collected Aedes aegypti in Yunnan Province, southwestern China - Zhang, HengDuan; Gao, Jian; Ma, Zu; Liu, Yuan; Wang, Ge; Liu, Qing; Du, YuTong; Xing, Dan; Li, ChunXiao; Zhao, Teng; Jiang, YuTing; Dong, YanDe; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Wolbachia is gram-negative and common intracellular bacteria, which is maternally inherited endosymbionts and could expand their propagation in host populations by means of various manipulations. Recent reports reveal the natural infection of Wolbachia in Aedes Aegypti in Malaysia, India, Philippines, Thailand and the United States. At present, none of Wolbachia natural infection in Ae. aegypti has been reported in China. Methods A total of 480 Ae. aegypti adult mosquitoes were collected from October and November 2018 based on the results of previous investigations and the distribution of Ae. aegypti in Yunnan. Each individual sample was processed and screened for the presence of Wolbachia by PCR with wsp primers. Phylogenetic trees for the wsp gene was constructed using the neighbour-joining method with 1,000 bootstrap replicates, and the p-distance distribution model of molecular evolution was applied. Results 24 individual adult mosquito samples and 10 sample sites were positive for Wolbachia infection. The Wolbachia infection rate (IR) of each population ranged from 0 - 41.7%. The infection rate of group A alone was 0%-10%, the infection rate of group B alone was 0%-7.7%, and the infection rate of co-infection with A and B was 0-33.3%. Conclusions Wolbachia infection in wild Ae. aegypti in China is the first report based on PCR amplification of the Wolbachia wsp gene. The Wolbachia infection is 5%, and the wAlbA and wAlbB strains were found to be prevalent in the natural population of Ae. aegypti in Yunnan Province.